Improved cryopreservation of Boer goat semen - Soe, Win Naing (2010)
Recently, interest in the cryopreservation of spermatozoa as a potential source of valuable genes has escalated to improve reproductive efficiency and productivity in livestock such as goats. The objectives of this study were to improve the quality of semen cryopreservation media, technique of cryopreservation, and to analyse the effects of various factors on goat sperm survival after freezing and thawing. To conduct this research, eleven Boer goats were used and semen was collected twice a week using an artificial vagina. For initial evaluation, the semen samples were assessed for volume, colour, consistency, mass activity, sperm concentration, sperm morphology, and percentage of motile spermatozoa. The qualified semen samples between one and two mL volume with a concentration of greater than 2.5 x 109 sperm/mL having >75% progressively motile sperm and >85% of the sperm with normal morphology were selected for cryopreservation. The qualified ejaculates were then diluted with the semen extenders and packed in 0.25 mL French straws. After equilibration, cooling and freezing procedures were carried out in a cooling chamber and liquid nitrogen. Two days later, the semen was thawed at 37°C for 30 sec and evaluated for the semen qualitative parameters such as motility, acrosome integrity, membrane integrity, live and normal spermatozoa percentages. Data were analyzed using ANOVA, followed by Tukey's post hoc test to determine significant differences in all the parameters between groups using the SPSS software system. The effects of four different sugars on semen quality were analyzed for the improvement of semen cryopreservation media in Boer goats. This study was conducted to analyze firstly the effect of two monosaccharides and two disaccharides in Boer goat semen cryopreservation, secondly, to investigate the combination effects of trehalose and other sugars, and finally to find out the most effective concentration of trehalose combination for Boer semen cryopreservation. The combination of 69.38 mM glucose and 198.24 mM trehalose conferred the practical and beneficial effects in cryopreservation of Boer goat spermatozoa. The effects of four cryoprotectants, different concentrations of glycerol and three glycerolization procedures with two cooling times for Boer goat semen evaluations, further fertility trials are required as ultimate test of improved cryopreservation.